Seabed Geoacoustic Analysis Using Scientific Single Beam Echosounder - La Elson La Elson; Henry M. Manik Manik; Totok Hestirianoto Hestirianoto; Sri Pujiyati Pujiyati (Jurnal Ilmiah Perikanan dan Kelautan)
Graphical Abstract